Digital Transformation of Mortgage Rights: Juridical Implications for Creditor Protection - Prehatini, Yuniar (PDIH Untag Semarang, 2025)
The development of digital technology has brought about a revolution in various aspects of life, including in the legal and land administration systems in Indonesia. This study examines the dynamics of the digital transformation of mortgage rights through the implementation of an electronic system (HT-el) initiated by the Ministry of Agrarian Affairs and Spatial Planning/National Land Agency (ATR/BPN). Using a normative legal method, the study explores the legal implications of this digital transformation on the legal protection of creditors. The results indicate that HT-el not only accelerates and simplifies the registration process for mortgage rights but also enhances transparency, accountability, and legal certainty for all parties involved. However, this digitalization is also accompanied by challenges such as data entry errors, human resource readiness, and electronic data security, which require further attention. Furthermore, the executory power inherent in electronic certificates provides creditors with an effective legal protection mechanism without having to go through lengthy court proceedings in the event of default. This study recommends strengthening regulations, intensive socialization, and improving technological capacity so that the digital transformation of mortgage rights can run optimally and provide maximum protection for creditors. This study is expected to serve as an important reference for policymakers and legal practitioners in addressing the digitalization of the land collateral system in Indonesia.